The novel use of inter‐maxillary fixation screws as denture abutments in a Parkinson's patient. (28th September 2016) - Beech, A.; Farrier, J.
Abstract: A 67‐year‐old male patient presented to our department with severe mentalis spasm secondary to Parkinson's disease unable to retain upper and lower complete dentures. Injection of the mentalis muscle with Botulinum Toxin (Botox ® ) gave limited improvement. Restrictions on the placement of dental implants within our Trust meant we were unable to offer them to the patient. We, therefore, placed two titanium IMF screws into both the mandibular and maxillary alveolar ridges. The patient's existing dentures were modified to accommodate the IMF screws enabling pleasing denture retention. The screw placement and denture addition procedures were carried out with excellent healing and no complications. The IMF screws remain stable in situ 9 months after placement. This technique for retaining complete dentures in a Parkinson's patient is simple and cost‐effective, with the added advantage of being easily reversible as their use does not prevent future implant placement.